LITERASI MEDIA DIGITAL PADA PELAKU UMKM DI KELURAHAN KALIABANG TENGAH - Dwiadi, Denianto; Widyastuti, Dina; MB, Galih; Yusnita, Jessy; Astuti, Hani; Sumartono, Sumartono (Universitas Esa Unggul, 2025)
AbstractDigital media has become a crucial need for various groups, including Usaha Mikro, Kecil dan Menegah/ UMKM (Micro, Small, Medium Enterprises / MSMEs). The Indonesian government's